2017
DOI: 10.1002/mnfr.201700116
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of glucagon receptor to plasma membrane increases in adipocytes of obese rats by soy protein; implications for glucagon resistance

Abstract: Soy protein increases GR recycling to the membrane of adipocytes and its ligand-binding and G protein selectivity, suggesting, it could be used in T2D dietary treatment to reestablish glucagon sensitivity in WAT, leading to the regulation of circulating glucagon levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Our findings in this study illustrated that after T2DM induction plasma glucagon level increased. This effect also was observed previously by other investigations . Mg therapy could not decrease plasma glucagon level in the T2DM animal model.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings in this study illustrated that after T2DM induction plasma glucagon level increased. This effect also was observed previously by other investigations . Mg therapy could not decrease plasma glucagon level in the T2DM animal model.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings demonstrated that Mg therapy downregulated GR in the T2DM group and this may improve insulin sensitivity. Third, the most important way to reduce insulin resistance is inhibition hepatic glucose production and gluconeogenesis via repressing gene expression of the enzyme G6Pase that is an enzyme that hydrolyzes glucose-6-phosphate, resulting in creation free glucose [47,48] and also Pepck major gluconeogenic enzymes [49] which converts pyruvate finally to glucose [47]. According to our investigation, Mg in T2DM rat models by increasing Glut4 mRNA and by decreasing G6pase, GR and Pepck mRNA could increase insulin sensitivity.…”
Section: Changes In Glut4 Protein Levelmentioning
confidence: 72%
See 1 more Smart Citation
“…In previous studies, we have observed improved cardiometabolic markers in healthy at-risk individuals after 4–8 week intake of MFD targeting low-grade inflammation [ 7 , 8 ]. The diet exerted also extensive impact on the plasma metabolome, particularly the lipidome [ 9 ]. However, whether these improvements can be associated with changes in the gut microbiota composition has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Soybean ( Glycine max ), which was first domesticated in the Northeastern China around 1100 B.C., is one of the most important crop plants for seed protein and oil content, and for its capacity to fix atmospheric nitrogen through symbioses with soil‐borne microorganisms . It is a rich source of bioactive compounds, some with potentially therapeutic antihyperlipidemic, antihyperglycaemic, antihypertensive, antioxidant, anti‐inflammatory, anticancer, antiobesity, and neuroprotective activities that support the biological plausibility for observational associations. As key active compounds, isoflavones (genistein, daidzein, and glycitein) are changed in the body to phytoestrogens, which are bioactive compounds with mildly estrogenic properties .…”
Section: Introductionmentioning
confidence: 99%